Improving Mathematics Learning Outcomes Using the Problem Based Learning Model on Fu nction Material in Grade XI - Ardilatus Sholehah; Shofia Hidayah; Suhartono (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to improve student learning outcomes in Function material through the application of the Problem Based Learning (PBL) model in class XI-C MAN 1 Probolinggo. This study is a Classroom Action Research (CAR) carried out in two cycles, each consisting of planning, action implementation, observation, and reflection. The subjects of the study were 24 students of class XI-C MAN 1 Probolinggo. Data were collected through observation of student activities and learning outcome tests at the end of each cycle. The results of the study showed an increase in student learning outcomes after the application of the problem based learning (PBL) model. The average value of learning outcomes increased from 66 in the pre-cycle to 71.5 in cycle I, and then increased again to 94.83 in cycle II. With learning completeness from 37.5% to 62.5%, and increased again to 100%. In addition, student activity and involvement in the learning process also showed a significant increase. Based on these results, it can be concluded that the application of the Problem Based Learning model is effective in improving student learning outcomes in Function material in class XI-C MAN 1 Probolinggo. This model can be an alternative innovative learning strategy to create an active, meaningful, and student-centered learning process.